Pengaruh Modal, Lama Usaha, Pendidikan, Serta Followers terhadap Tingkat Pendapatan Pelaku Usaha Mikro dan Kecil pada Marketplace Shopee di Kota Banjarmasin - Amalia , Sabda Riski; Zulfaridatulyaqin, Siti Mutmainnah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
The development of technology in the digital age now encourages the perpetrators of micro and small businesses to enter the online market, most specifically in Banjarmasin. Some business actors utilize the application Shopee to market their trades to expand the market reach. This leads to curiosity about the income of micro and small businesses selling in the Shopee app and want to see what factors affect the revenue. The population in this research is the micro and small business actors in Banjarmasin City that sell in the online marketplace Shopee; this study uses as many as 30 people to be samples taken with accidental sampling using the OLS analysis method multiple linear regression. This research aims to analyze the factors that affect the income of micro and small enterprises selling in the online shop marketplace in Banjarmasin, in this research using 4 independent variables, among others, the length of business in the online marketplace Shopee, education as well as the followers while for its dependencies variable this research using the income of micro and small business actors. Therefore, this research is a descriptive study. Results in this research show the variable of independent capital and the length of effort has a significant influence on the income of micro and small business actors in the city of Banjarmasin selling in the online marketplace Shopee, while the independent variables education and followers have no influence on the revenue of micro and small business actors in the city of Banjarmasin selling in the online marketplace Shopee.